2018
DOI: 10.1002/ceat.201700303
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Ethanol Purification Using Polymeric Membranes and a Pervaporation Process

Abstract: A comprehensive computational fluid dynamics simulation was developed for the rational design of a bioethanol purification system using a pervaporation process by tailoring the hydrodynamics of the process. The process involves the removal of water from a water/ethanol liquid mixture using a dense polymeric membrane. The model domain was divided into two compartments comprising the feed and the membrane. To describe water transport in the feed solution, the Maxwell-Stefan approach was used, whereas for mass tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The swelling degree (DS) can be calculated as Eq. (1). DS values of the membrane with the same CG loading were measured at least for three times, the average result was taken as the final one.…”
Section: Swelling Degree Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The swelling degree (DS) can be calculated as Eq. (1). DS values of the membrane with the same CG loading were measured at least for three times, the average result was taken as the final one.…”
Section: Swelling Degree Testsmentioning
confidence: 99%
“…The reduced equipment size over production capacity results in lower capital cost as well. With the advantages of energy‐saving and process intensification, PV has played an increasingly vital role for separating liquid‐liquid mixtures, especially for azeotropic mixtures including ethanol/water mixtures .…”
Section: Introductionmentioning
confidence: 99%
“…The discretized geometry of process is shown in Figure . UMFPACK was used as the direct solver for the solution of the equations . A computer with central processing unit (CPU) speed of 3.5 GHz and 32 GB of random‐access memory (RAM) was used for the numerical calculations, while adaptive mesh tool in COMSOL software was used in order to find the optimum number of meshes for the model domain and implement the mesh independence test.…”
Section: Model Of Processmentioning
confidence: 99%
“…Separation of benzoic acid from a liquid solution using porous membranes was studied by Aghrahari et al , and high performance was observed. It has been indicated that the porous polymeric membranes provide high separation efficiency and can be used for water‐ and wastewater‐treatment applications , .…”
Section: Introductionmentioning
confidence: 99%